Globalization and the Pan-American highway: Concerns for the Panama-Colombia border region of Darién-Chocó and its peoples (2022)
eng: The Darien - Chocó Region is a privileged but abandoned region - privileged because it enjoys rich biological and cultural diversities. As one of the most species-rich regions on earth, the region truly deserves its natural world heritage classification.' It is a biological, political, and economic crossroads that connects North and South America and the Atlantic and Pacific Oceans. The region suffers, however, from a number of unfortunate realities. It is isolated from centers of power in Colombia and Panama, and government services and transportation infrastruc- ture are clearly deficient. Active colonization and deforestation fronts eat at the tropical forest ecosystem on both sides of the bor- der along existing roads. The region's communities display high levels of poverty and unsatisfied basic human needs. The area is rife with conflicts over land, power, and geopolitics. The Colombian portion of the region has been the scene of extreme political violence for more than twenty years that has caused a grave humanitarian crisis for indigenous and Afro-Colombian populations.